Ukraine - EU: Historical and Legal Analysis of European Integration - Andriy Redko (Vasyl Stefanyk Precarpathian National University, 2017)
This article analyzes the European integration of Ukraine in the context of the processes of integration and globalization. The main attention is paid to the European Union law and laws of Ukraine and the interaction between them. Two processes have been distinguished: the integration of the legislation in the European Union and the adaptation of the Ukrainian legislation to the EU legislation.